2022
DOI: 10.21203/rs.3.rs-1198887/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional interdependence of the actin regulators CAP1 and cofilin1 in control of dendritic spine morphology

Abstract: The vast majority of excitatory synapses are formed on small dendritic protrusions termed dendritic spines. Dendritic spines vary in size and density that are crucial determinants of excitatory synaptic transmission. Aberrations in spine morphogenesis can compromise brain function and have been associated with neuropsychiatric disorders. Actin filaments (F-actin) are the major structural component of dendritic spines and therefore actin-binding proteins (ABP) that control F-actin dis-/assembly moved into the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Studies from us and others identified cofilin1 and ADF as key actin regulators in neurons (Rust, 2015a, b), whose inactivation shifted the actin equilibrium towards Factin (Rust et al, 2010;Flynn et al, 2012;Wolf et al, 2015). Further, we recently demonstrated an interaction of cofilin1 with both CAP2 and CAP1 in neurons (Pelucchi et al, 2020;Schneider et al, 2021b;Heinze et al, 2022). We therefore expected increased SRF activity in neurons lacking i) cofilin1, ii) cofilin1 and ADF, iii) CAP2 and/or iv) CAP1.…”
Section: Cap1 But Not Adf/cofilin or Cap2 Is Crucial For Neuronal Srf...mentioning
confidence: 73%
See 3 more Smart Citations
“…Studies from us and others identified cofilin1 and ADF as key actin regulators in neurons (Rust, 2015a, b), whose inactivation shifted the actin equilibrium towards Factin (Rust et al, 2010;Flynn et al, 2012;Wolf et al, 2015). Further, we recently demonstrated an interaction of cofilin1 with both CAP2 and CAP1 in neurons (Pelucchi et al, 2020;Schneider et al, 2021b;Heinze et al, 2022). We therefore expected increased SRF activity in neurons lacking i) cofilin1, ii) cofilin1 and ADF, iii) CAP2 and/or iv) CAP1.…”
Section: Cap1 But Not Adf/cofilin or Cap2 Is Crucial For Neuronal Srf...mentioning
confidence: 73%
“…These data suggested a crucial role for CAP1, but not for CAP2 in regulating neuronal SRF activity. Since previous studies revealed a cooperation of cofilin1 and CAP1 in actin subunit dissociation and in neuron morphology (Kotila et al, 2019;Shekhar et al, 2019;Schneider et al, 2021b;Heinze et al, 2022), we tested whether compound inactivation of both ABP further increased SRF activity. Interestingly, Creexpressing Cfl1 flx/flx /CAP1 flx/flx neurons (Cfl1/CAP1-dKO) displayed an increase in SRF reporter activity very similar to CAP1-KO neurons (Fig.…”
Section: Cap1 But Not Adf/cofilin or Cap2 Is Crucial For Neuronal Srf...mentioning
confidence: 99%
See 2 more Smart Citations